Personal Dhikr As a Result of the Student Religious Character Strengthening Program at Madrasah Aliyah Plus Az-Zikra Bogor - Ruh Halil Ahmad Ibrahim; Abas Mansur Tamam; Wido Supraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This study aims to analyze the religious character education program at Madrasah Aliyah Plus Az-Zikra Bogor, which produces students who have a religious character, namely personal dhikr, as a result of a program to strengthen religious character education. The conclusion of this study is that the dhikr-based religious character education strengthening program for Madrasah Aliyah Plus Az-Zikra Bogor has three components that are integrated into co-curricular and extra-curricular activities. The first component is practicing the seven daily sunnahs, namely tahajjud prayers, and tadabbur Al-Qur'an, congregational prayers at the mosque, dhuha prayers, almsgiving, maintaining ablution and making more forgiveness. The second component is always practicing the wirid of the seven chosen surah, namely, surah Yaasin's, surah Ar-Rahman's, surah Al-Waqiah's, surah Al Mulk's, surah Al-Jin's, surah Al-Muzzammil's, and surah Al-Fajr's. The third component is the Santri Prayer as a special prayer for students at Madrasah Aliyah which is read together when they finish the five daily prayers. So that by integrating these three components, Madrasah Aliyah Plus Az-Zikra Bogor can produce graduates who have religious character based on dhikr or can be called personal dhikr.